FINANCIAL LITERACY AND HOUSEHOLD SAVING BEHAVIOR: A COMPARATIVE STUDY OF URBAN AND RURAL COMMUNITIES IN INDONESIA - Luthfiar Ramiady; Hendri Bin Muhammad Nur (SUMBER INFORMASI MANAJEMEN BISNIS DAN AKUNTANSI, 2025)
This study examines the relationship between financial literacy and household saving behavior in Indonesia, focusing on disparities between urban and rural communities. Employing a mixed-methods design, the research combines survey data from 500 households with in-depth interviews to capture both quantitative patterns and qualitative insights. The findings reveal significant literacy gaps: 65% of urban households demonstrate a basic understanding of financial concepts compared to only 35% of rural households. These disparities translate into distinct saving practices, with urban families more likely to engage in formal banking and investment, while rural households rely on informal mechanisms with limited long-term security. Cultural norms, digital access, and income levels further mediate these dynamics. Notably, households participating in targeted financial education programs reported a 20% increase in savings within six months, underscoring the transformative potential of structured interventions. The study highlights the dual role of technology as an enabler in urban contexts and a barrier in rural areas, pointing to the urgent need to address the digital divide. By integrating cultural sensitivity, technological inclusion, and community-based approaches, policymakers and educators can design more effective strategies to enhance financial literacy. Beyond immediate saving behavior, the study emphasizes the broader implications of literacy for economic resilience, equity, and sustainable development.